Incidental Histological Diagnosis of Acute Rheumatic Myocarditis: Case Report and Review of the Literature - Spina, Guilherme S.; Sampaio, Roney O.; Branco, Carlos E.; Miranda, George B.; Rosa, Vitor E. E.; Tarasoutchi, Flávio (Frontiers in Pediatrics, 2014)
Rheumatic fever remains endemic in many countries and frequently causes heart failure due to severe chronic rheumatic valvular heart disease, which requires surgical treatment. Here, we report on a patient who underwent an elective surgical correction for mitral and aortic valvular heart disease and had a post-operative diagnosis of acute rheumatic carditis. The incidental finding of Aschoff bodies in myocardial biopsies is frequently reported in the nineteenth-century literature, with prevalences as high as 35%, but no clinical or prognostic data on the patients is included. The high frequency of this finding after cardiac surgery in classical reports suggests that these patients were not using secondary prophylaxis for rheumatic fever. We discuss the clinical diagnosis of acute rheumatic myocarditis in asymptomatic patients and the laboratorial and imaging methods for the diagnosis of acute rheumatic carditis. We also discuss the prognostic implications of this finding and review the related literature.